2010
DOI: 10.1007/978-3-642-16233-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-Boltzmann Simulation of the Shallow-Water Equations with Fluid-Structure Interaction on Multi- and Manycore Processors

Abstract: Abstract. We present an efficient method for the simulation of laminar fluid flows with free surfaces including their interaction with moving rigid bodies, based on the two-dimensional shallow water equations and the Lattice-Boltzmann method. Our implementation targets multiple fundamentally different architectures such as commodity multicore CPUs with SSE, GPUs, the Cell BE and clusters. We show that our code scales well on an MPI-based cluster; that an eightfold speedup can be achieved using modern GPUs in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…The benchmarks of the solver configurations include comparisons with basic linear algebra kernels to evaluate different performance and memory characteristics. We refer to previously published work for an analysis in terms of mass conservation, a comparison with external codes and some other aspects not covered here [3,5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The benchmarks of the solver configurations include comparisons with basic linear algebra kernels to evaluate different performance and memory characteristics. We refer to previously published work for an analysis in terms of mass conservation, a comparison with external codes and some other aspects not covered here [3,5].…”
Section: Resultsmentioning
confidence: 99%
“…We have evaluated our approach with a multigrid solver for the prototypical Poisson problem, and an explicit finite difference solver for the shallow water equations (SWE). In this paper, we go significantly further and apply newly developed and improved backends [3,4] to the more challenging task of interactive fluid dynamics (CFD) using a coupled Lattice-Boltzmann (LBM) fluid structure interaction (FSI) application. We aim at exploiting the full performance of hybrid single nodes, equipped with CPUs and GPUs or the Cell BE, an important prerequisite towards efficient large-scale computations.…”
Section: Paper Contribution and Paper Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are already GPU implementations as [17], where it was adapted using textures; but more recently, with the advent of general programmability of GPUs we find CUDA implementations like [18] and [19]. [20] proposed an alternative kernel implementation to reduce memory usage and [21] targeted multiple different parallel architectures using higher-level libraries for solving the LBMSW model.…”
Section: Related Workmentioning
confidence: 99%
“…Geist et al developed a real-time approach for wave surface generation and attained 25 Hz for grid of size 1024 2 [19]. Geveler et al developed LBM based approach for simulating laminar flow with free fluid surface on multi-core CPU and many-core GPU processors and reported a factor of 8 speed-up on GPU code with respect to multi-threaded CPU code [20]. Gladkov et al reported direct simulation Monte Carlo (DSMC) for solving Boltzmann equations on per particle basis (to solve rarefied fluid flow problems) by using GPU to obtain speed-up by a factor of 65 over serial implementation.…”
Section: Fluid-rigid Body Interaction Simulationmentioning
confidence: 99%